Pengadaan Taman Baca Bagi Anak-Anak dan Remaja Usia Sekolah di Desa Oetulu Nusa Tenggara Timur - Botha, Hendrikus Hironimus; Fritantus, Yohanes; Rembu, Yoakim (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This Community Service activity aims to improve literacy skills for school-age children and adolescents in Oetulu Village, Musi District, North Central Timor Regency. Community service is carried out in several stages, namely coordinating/communicating with the Oetulu Village Government, Surveying and determining the location of the reading park, Procurement of books and supporting facilities for the reading park, Arranging the location of the reading park, Operation of the reading park by the community service team and the community and Assistance in managing the reading park. The results of the implementation of community service activities carried out in several stages are the availability of a community reading park for school-age children and adolescents in Oetulu Village.